Alcohol and substance use among transgender women in San Francisco: Prevalence and association with human immunodeficiency virus infection. (14th March 2014) - Santos, Glenn‐Milo; Rapues, Jenna; Wilson, Erin C.; Macias, Oscar; Packer, Tracey; Colfax, Grant; Raymond, Henry Fisher
Abstract Introduction and Aims Alcohol and substance use can have negative health consequences among both human immunodeficiency virus (HIV)‐positive and ‐negative individuals, and are associated with behaviors that facilitate HIV transmission and acquisition. The relationship of substance use and HIV is well documented among key populations at risk for HIV. However, although transwomen (male‐to‐female transgender) are disproportionately impacted by HIV, this overlap remains understudied in this population. We sought to evaluate the association between HIV, alcohol and substance use among transwomen. Design and Methods We conducted a secondary data analysis of Respondent Driven Sampling study which collected information on self‐reported alcohol and substance use among 314 transwomen. We used multivariable logistic regression to assess relationship between HIV infection and classes and patterns of alcohol and substance use. Results We found that 58% of transwomen used alcohol, and 43.3% used substances. The most common substances used were: marijuana (29%), methamphetamine (20.1%), crack cocaine (13.4%), and 'club drugs' (13.1%). Transwomen who reported any methamphetamine use [adjusted odds ratio (AOR) 3.02 (95% confidence interval (CI) = 1.51–6.02)], methamphetamine use before or during anal intercourse [AOR 3.27 (95% CI = 1.58–6.77)], and at least weekly methamphetamine use [AOR 3.89 (95% CI = 1.64–9.23)] had significantly greater odds of testing positive for HIV. Discussion and Conclusions Transfemales have high prevalence of alcohol and substance use; those tested positive for HIV used significantly more methamphetamine in general, and in conjunction with sex. Given the disproportionate prevalence of HIV and substance use in this population, interventions aimed at addressing both substance use and HIV risk among transwomen are urgently needed. [Santos G‐M, Rapues J, Wilson EC, Macias O, Packer T, Colfax G, Raymond HF. Alcohol and substance use among transgender women in San Francisco: Prevalence and association with human immunodeficiency virus infection. Drug Alcohol Rev 2014;33:287–295]